Trends in multiple health complaints in Polish adolescents in light of data from 30 European countries and Canada (2002-2018) - Mazur, Joanna; Klanšček, Helena Jeriček; Augustine, Lilly; Porwit, Katarzyna; Sigmund, Erik; Šmigelskas, Kastytis (Journal of mother and child, 2021)
BACKGROUND: Adolescence is a sensitive period accompanied by rapid developmental changes that can result in health complaints. The aim of the study was to describe the trend of subjective health complaints (HBSC-SCL) of Polish adolescents compared to their peers from 30 other countries and to rank all countries based on a proposed standardised measure. MATERIAL AND METHODS: Data from the Health Behaviour in School-Aged Children (HBSC) study collected from 2002 to 2018 were used. The overall number of respondents from 30 countries in the combined sample from five quadrennial rounds was 773,356, including 49.2% boys and 50.8% girls. The HBSC-SCL is a non-clinical measure consisting of eight health complaints, usually analysed in two dimensions of psychological and somatic symptoms. Linear regression analysis was applied to assess the significance of trends of the total index and two subindices in the combined sample and individual countries. RESULTS: A significant increasing trend for the eight-item index appeared in Poland only in 13- and 15-year-olds, while only among 15-year-olds in the combined sample from 30 countries. Standardised country rank varied between -1.85 and 2.48 (worst). The countries that achieved extreme negative values (>=1) are France, Hungary, Italy, and Sweden, and the rank for Italy is considerably higher than for other countries. In Poland, the standardised rank for psychological symptoms exceeded the threshold of +1 in 2018. CONCLUSIONS: The HBSC-SCL index could be useful for monitoring change in adolescent mental health. The proposed method of ranking may allow a broader view of the differences and similarities between countries and help to identify those performing unfavourably against cross-country patterns.
Keywords: trends; Švédsko; Humans; chování mladistvých; dítě; international data; Sweden; Child; Schools; Female; Polsko; lidé; Europe; Poland; ženské pohlaví; Male; školy; Adolescent Behavior; subjective complaints; Adolescent; mužské pohlaví; mental health; Evropa; mladiství